The Impact of volition on the relative values of reinforcers in operant conditions of a fluency period and a stuttering response - Purushothama G (Journal of All India Institute of Speech and Hearing, 1970)
The impact of volition was measured operationally using changing values of reinforcers on both fluency and stuttering. The ABA paradigm was used in testing five subjects Jor this purpose. With reinforcement, it was seen, only fluency increased and not the stuttering response—repetition. The influence of volition in learning is discussed.